Detecting granulated fruit by measuring dual-frequency back scattered waves - Kittiyanpunya, C.; Phongcharoenpanich, C.; Krairiksh, M. (My University, 2017)
Granulation is a kind of defection in fruits that must be non-destructively detected. Electromagnetic wave measurement is a feasible technique for in-situ measurement. With thick peel, it is necessary to eliminate the effect of peel so that sole effect of variation of pulp can be detected. This paper presents the simulated scattering coefficient from fruit with dual-frequency that exhibits more obvious results than the single-frequency measurement. The results lead to the appropriate design of a sensor for granulation detection.
Keywords: reflectometer; scattered wave; scattering coefficient